Deregulated enhancer-promoter communication in cancer through altered nuclear architecture - Seufert, Isabelle; Vargas, Claire; Wille, Sina Jasmin; Rippe, Karsten (International journal of cancer, 2026)
Enhancers are critical regulators of gene expression. Structural variations in cancer genomes can lead to enhancer hijacking, where oncogenes are activated by mistargeted enhancer activity. Novel enhancer-promoter interactions may also arise through chromosomal rearrangements that create extrachromosomal DNA elements. Additionally, fusion proteins and other mutation-induced alterations in protein properties can lead to the aberrant assembly of proteins into large complexes on the size scale of 0.1-1 μm termed onco-condensates. Transcription factors and co-activators accumulate with cis-regulatory elements in these structures, driving oncogenic programs. Here, we review current evidence of how altered genome architecture and macromolecular assembly result in deregulated enhancer-promoter communication. We discuss emerging strategies to exploit these mechanisms for clinical applications.
Veröffentlicht: 12 April 2025
Gesehen am 03.12.2025